PENGARUH BRAIN GYM TERHADAP KUALITAS TIDUR PADA ANAK 7-8 TAHUN DI SD MUHAMMADIYAH 04 DEPOK - Muhammad Yusuf (2022)
Sleep is a basic human need, including children. Good sleep in children will get growth hormone in optimal amounts. Lack of sleep time or duration is one part of sleep disorders in school children Is there any influence Brain gym has on the quality of sleep in children aged 7-8 years To find out the effect Brain gym can help transition from sleep to wake up in children aged 7-8 years Research Methods: This research uses Pre-experimental design This design is said to be a pre-experimental design because it is not yet a real experiment because there are external variables that also influence the formation of the dependent variable. With the form of One - Group Pretest-Posttest Design (One Group Pretest-Posttest) Results: Paired Sample T-test shows the influence of Brain Gym on sleep quality of children aged 7-8 years of 0.000 <0.05 then H0 is rejected and H1 is accepted So it can be drawn the conclusion that there is an average difference between sleep quality before (pretest) and sleep quality after (posttest), which means that there is an effect of brain gym on sleep quality in children 7-8 years old.